Morally literate: Forging communities of moral sensitivity and care through Theatre Pedagogy - Mamali, Evi (Epistēmēs Metron Logos, 2023)
This article presents the fundamental aspects of theatre as an art form as well as a pedagogical approach and analyzes the way they shape learning in educational settings. It, then, focuses on key features of moral literacy explaining how young learners must learn to think in the context of moral education. At the last section the article explores how Theatre Pedagogy practices can be conducive to moral literacy. It is argued that a number of aspects of multi-faceted Theatre Pedagogy, such as corporeality, experiential and playful inquiry, the aesthetic and semiotic dimension and its participatory nature among others, have a strong impact on moral understanding and should be integrated in youth’s moral education.